PELATIHAN PEMANFAATAN TEKNOLOGI DALAM EDUKASI DIABETES AWARENESS BAGI PENANGGUNG JAWAB USAHA KESEHATAN SEKOLAH (UKS) DI PUSKESMAS KOTA PADANG - Hema Malini; Devia Putri Lenggogeni; Fauziah Qifti (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2021)
The increasing prevalence of diabetes mellitus (DM) is a global health problem. Currently, the incidence of diabetes mellitus in adolescents is rising. Nowadays, diabetes mellitus awareness in adolescents lacks attention. Awareness is the most important thing to prevent diabetes mellitus. Health education is one of the techniques to increase awareness among adolescents. The previous study showed that using social media such as WhatsApp can increase adolescents' awareness about the causes and prevention of diabetes. This community service activity was developing a technology-based health education model that public health centres can carry out to increase diabetes awareness of adolescents. The use of technology is a part of today's life, so the development of technology-based diabetes awareness education models is expected to be a model of education and can be helpful to increase adolescent awareness about diabetes mellitus. This activity was carried out by delivering technology in health education programs and applying WhatsApp groups. This activity was expected to provide information for health workers in carrying out educational programs by utilizing technology.